DEVELOPMENT OF ANIMATED VIDEOS AS AN EFFORT TO PREVENT ONLINE SEXUAL VIOLENCE AT THE UPT SPF SMP NEGERI 8 MAKASSAR - Irma Firgasari; Abdullah Sinring; Sahril Buchori (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to determine: 1) the overview of needs for developing animated videos as an effort to prevent sexual violence in the online realm, 2) the prototype of animated videos as a medium for prevention, 3) the validity of the animated videos, and 4) the practicality of these videos. The research approach used the Borg & Gall R&D model with a mixed quantitative and qualitative method. The research subjects consisted of two Guidance and Counseling lecturers, two Educational Technology lecturers, and two school counselors. Data was collected through needs questionnaires, expert validation sheets, observations, interviews, and documentation of trial results, analyzed descriptively. The findings show that: 1) animated video development is highly needed by students and counselors; 2) the prototype is a 10-minute MP4 video made using Cap Cut, Canva, and Clipvideo; 3) the animated video is declared valid and practical; 4) it facilitates counselors in providing information services to prevent online sexual violence.